The baby bequest [large type] - Cote, Lyn (Center Point Large Print, 2013)
Schoolteacher Ellen Thurston never expected to find love in Pepin, Wisconsin. But the moment she discovers a baby boy outside her door, it's love at first sight. While the townfold don't approve of Ellen as a single mother, what worries her most are her feelings for the handsome farmer who defends her decision to keep the child.